2020
DOI: 10.3389/fgene.2020.00407
|View full text |Cite
|
Sign up to set email alerts
|

An Adaptive Sparse Subspace Clustering for Cell Type Identification

Abstract: The rapid development of single-cell transcriptome sequencing technology has provided us with a cell-level perspective to study biological problems. Identification of cell types is one of the fundamental issues in computational analysis of single-cell data. Due to the large amount of noise from single-cell technologies and high dimension of expression profiles, traditional clustering methods are not so applicable to solve it. To address the problem, we have designed an adaptive sparse subspace clustering metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 40 publications
(42 reference statements)
0
10
0
Order By: Relevance
“…erefore, one can categorize these methods into two groups according to the strategy used to obtain a given data's lowdimensional coefficient matrix. e first group has methods like those mentioned in [10,[12][13][14], which use the L1-norm regularization [8] to acquire the coefficient matrix. For example, Zhang et al [10] proposed a spectral-spatial sparse subspace clustering algorithm for hyperspectral remote sensing images, which obtains a final clustering by applying a spectral clustering algorithm on an adjacent matrix.…”
Section: Related Workmentioning
confidence: 99%
“…erefore, one can categorize these methods into two groups according to the strategy used to obtain a given data's lowdimensional coefficient matrix. e first group has methods like those mentioned in [10,[12][13][14], which use the L1-norm regularization [8] to acquire the coefficient matrix. For example, Zhang et al [10] proposed a spectral-spatial sparse subspace clustering algorithm for hyperspectral remote sensing images, which obtains a final clustering by applying a spectral clustering algorithm on an adjacent matrix.…”
Section: Related Workmentioning
confidence: 99%
“…Clustering has been well studied in recent decades and many popular methods have been proposed, like K-Means (7), spectral clustering (8; 9; 10) and subspace clustering (11; 12). However, directly using these methods to cluster scRNA-seq data usually fails to obtain desirable results.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, subspace clustering [19,20] has also been successfully applied in cell type identification. SinNLRR [21] and AdaptiveSSC [22] both used subspaces to learn the similarity between cells. Butler et al [23] identified the highly variable features and constructed a KNN graph based on the Euclidean distance in latent spaces, and the edge weights between any two cells were defined based on the Jaccard similarity.…”
Section: Introductionmentioning
confidence: 99%
“…SAME-clustering [26] combined a maximally diverse subset of four clustering solutions obtained from five individual clustering methods, then the subset was combined with the expectation-maximization (EM) algorithm to build an ensemble clustering solution. Among all these methods, we find that hierarchical clustering [10,15,16,18,25,[27][28][29] and graph-based clustering [30][31][32][33][34] such as spectral clustering and Louvain community detection algorithm are the most popular approaches in the downstream clustering analysis [9,12,[21][22][23][24]35] . Additionally, densitybased clustering is also widely used in scRNA-seq data analysis for the identification of outlier cells [36,37] .…”
Section: Introductionmentioning
confidence: 99%